THE DEVELOPMENT OF TEACHING MATERIAL BASED ON CONCEPT MAPS TO TRAIN OF HIGHER ORDER THINKING SKILLS CHEMICAL EDUCATION OF SUDENTS IN THE SUBJECT MATTER OF ISOMER - Ismono, Ismono; Suyatno, Suyatno; Tukiran, Tukiran (JCER (Journal of Chemistry Education Research), 2017)
This study is a research and development of teaching materials of concept map-based on inquiry strategy with the aim of testing the feasibility of the device through three indicators, namely: (a) the validity, (b) the effectiveness, and (c) the practicality. The subjects used in this study are three experts namely 2 professors and 1 doctor, and 24 students of chemical education class who take college organic chemistry 1. Research carried out for four weeks. The results showed that the teaching material to developed: (1) to have the validity of the theory with good category; (2) has practicality in learning; (3) has the effectiveness, because capable of improving learning achievement and higher level thinking skills shown by the increasing score gain in the category of medium or high.